Small crumbled diet versus powdered diet in restricted feeding management of juvenile Nile tilapia - doi: 10.4025/actascianimsci.v35i2.16767 - Lima, Francisco Roberto dos Santos; Akao, Michael Masaki Freitas; Oliveira-Segundo, José Nacélio; Sá, Marcelo Vinícius do Carmo e (Acta Scientiarum. Animal Sciences, 2012)
The pellet size of the diet can affect both fish growth performance and the water quality of the rearing units. The present work assessed the effects of feeding juvenile Nile tilapia, Oreochromis niloticus (L.) a small crumbled diet (SCD; 0.8 mm) on water quality and growth performance. Fish were reared for six weeks in twenty 250-L polyethylene outdoor tanks at a density of 10 juveniles tank-1 (40 fish m-3). There were two feeding rates (standard and restricted) and two types of artificial fish diet (powdered and SCD). The standard feeding rates were reduced by 30% for restricted feeding. The concentrations of free CO2, reactive phosphorus, total ammonia nitrogen (TAN) and nitrite were higher in the full-fed tanks relative to the restricted-fed tanks. In the standard feeding rate groups, those tanks fed SCD had lower TAN and nitrite concentrations than tanks fed a powdered diet. The final body weight and specific growth rate of fish fed a restricted SCD were higher than the full-fed tanks. The higher levels of food waste in the powdered-diet tanks lead to impairment of fish growth performance.